9 - A New Learning Experience of Training in the Social Sciences Using Online Platforms in Low-Resource Settings: A Pandemic Experience at Busitema University, Uganda - Alice Nakiyemba; Musobya Moses; Masaba Sowedi (CODESRIA Bulletin, 2023)